Influence of riparian grazing on channel morphology and riparian health of the Lower Little Bow River. Issue 1 (2nd January 2018) - Miller, Jim; Curtis, Tony; Chanasyk, David; Willms, Walter
Abstract : Unmanaged riparian grazing may negatively impact rivers. The objective was to determine the influence of riparian grazing by cattle on selected channel morphology properties and riparian health of the Lower Little Bow River in southern Alberta. Three study reaches with increasing levels of riparian grazing impact were selected: (1) a fenced reach with cattle exclusion (2001–2012) followed by two years (2013–2014) of periodic grazing of the riparian pasture, (2) an unfenced and grazed reach with low cattle impact, and (3) an unfenced and grazed reach with high cattle impact. Selected channel morphology properties were measured for 3 years (2013–2015), and streambank erosion was measured over 6 years (2009–2014). The riparian health of the fenced reach was also assessed before and after 4, 8 and 11 yr of cattle exclusion, and then after 2 yr of periodic grazing. The findings generally supported the hypothesis that reduced or no riparian grazing impact would significantly (P ≤ 0.10) increase bank undercut, water depth, bankfull depth and mean-weight diameter of riverbed sediment, and decrease flow width, flow width:depth ratio, bankfull width, bankfull width:depth ratio and bank erosion. The overall riparian health score of the fenced reach was increased from 65% (healthy but with problems) prior to fencing to 85% (healthy) after 11 yr of cattle exclusion, but then decreased to 78% (healthy but with problems) after two years of periodic grazing. Exclusion fencing generally improved most channel morphology variables and riparian health. However, non-utilization of the forage resource, excess litter build-up and greater fire risk, and increased disturbance-caused plants and invasive species were serious management concerns. These issues might be alleviated by periodic grazing of the riparian pasture, but the long-term effect of this practice on channel morphology and riparian health requires further research.